Childhood adiposity and adolescent sex steroids in the Exploring Perinatal Outcomes among Children study. (14th July 2019) - Kim, Catherine; Harrall, Kylie K.; Glueck, Deborah H.; Shumer, Daniel; Dabelea, Dana
Abstract: Objective: It is unclear how childhood adipose tissue deposition influences sex hormone profiles in later adolescence. Design: Prospective cohort study. Participants: Children (n = 418) with a mean age of 10.5 (1.5) years at visit 1 and 16.7 (1.2) at visit 2 in the Exploring Perinatal Outcomes among Children (EPOCH) Study. Measurements: We used reverse‐scale Cox proportional hazard models to assess associations between pubertal dehydroepiandrosterone (DHEA), testosterone (T), and oestradiol (E2) and childhood‐to‐puberty rate of change in visceral (VAT) and subcutaneous adipose tissue (SAT). Models stratified by sex and adjusted for childhood adiposity, maternal factors, birthweight and pubertal onset, and then further adjusted for insulin, luteinizing hormone (LH), leptin and hepatic fat fraction. Results: Among boys, more rapid accumulation of either VAT or SAT was associated with lower testosterone at visit 2 (HR 0.86, and .96, respectively, both P  < .0001), independently of race/ethnicity, LH, leptin and hepatic fat fraction. Among boys, more childhood VAT was associated with lower testosterone in adolescence (HR 0.98, P  = .003), but this association did not persist after adjustment for leptin or insulin. No associations were observed between either fat measure and oestradiol or DHEA in boys. In girls, no associations between childhood fat or fat accumulation and sex hormones were observed. Conclusions: More rapid accumulation of fat is associated with lower testosterone in boys. These associations suggest that fat growth influences androgen profiles in adolescent boys. Since fat accumulation is a modifiable risk factor, the study results provide a possible intervention target and time period for improving adult health.